2014
DOI: 10.1007/s11065-014-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency in Focal Epilepsy: A Systematic Review and Meta-analysis

Abstract: Testing of verbal fluency is currently part of standard presurgical neuropsychological assessment for patients with focal epilepsy. However, to date no systematic review has been conducted on semantic (SVF) and phonemic verbal fluency (PVF) in this patient group. The present review compares verbal fluency between healthy control subjects and subgroups of adult presurgical patients with focal epilepsy according to lateralisation and localisation of the dysfunction. PubMed was searched with a comprehensive searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 81 publications
4
35
0
1
Order By: Relevance
“…This finding is in contrast to our hypothesis, as we expected, based on the consistent direction of asymmetry in language, that hippocampal activity would be lateralized to the left side, particularly during semantic fluency. In the literature on verbal fluency in temporal lobe epilepsy (TLE), a recent systematic review and meta-analysis demonstrated similar findings to ours (Metternich et al, 2014). Like us, the authors of this review were surprised by the findings as they noted that "the impairment in right TLE (RTLE) patients was more pronounced than expected" (Metternich et al, 2014, p. 211, italics added).…”
Section: Discussionsupporting
confidence: 70%
“…This finding is in contrast to our hypothesis, as we expected, based on the consistent direction of asymmetry in language, that hippocampal activity would be lateralized to the left side, particularly during semantic fluency. In the literature on verbal fluency in temporal lobe epilepsy (TLE), a recent systematic review and meta-analysis demonstrated similar findings to ours (Metternich et al, 2014). Like us, the authors of this review were surprised by the findings as they noted that "the impairment in right TLE (RTLE) patients was more pronounced than expected" (Metternich et al, 2014, p. 211, italics added).…”
Section: Discussionsupporting
confidence: 70%
“…These changes are based on the neural plasticity phenomenon that can take place in TLE patients over the years (Berg & Scheffer, ). The reorganization patterns can be more or less cognitively efficient and various degrees of language and memory deficits have been described in patients with mTLE (Alessio et al, ; Jaimes‐Bautista, Rodríguez‐Camacho, Martínez‐Juárez, & Rodríguez‐Agudelo, ; McAndrews & Cohn, ; Metternich, Buschmann, Wagner, Schulze‐Bonhage, & Kriston, ). For instance, Hoppe et al determined that language and memory were the most affected functions in a large cohort of epileptic patients mainly composed of mTLE (Hoppe, Elger, & Helmstaedter, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed by results of studies conducted on patients with Alzheimer's disease and epilepsy. Such patients achieved lower scores in verbal fluency tasks due to verbal memory dysfunction (Herbert et al, 2014;Metternich et al, 2014;Tsantali & Economidis, 2014). Compared to healthy controls, schizophrenia patients create fewer clusters in semantic fluency test (Neill et al, 2014;Nicodemus et al, 2014;Sung et al, 2012).…”
Section: Or Ruff Figural Fluencymentioning
confidence: 96%
“…Quantitative and qualitative results which can be obtained by means of those tests can be used to analyse the nature of cognitive and executive disorders (Stuss & Knight, 2013). Although there exist extensive data indicating various reasons for schizophrenia patients' low scores in verbal fluency tests (Bozikas, Kosmidis, & Karavatos, 2005;Dibben, Rice, Laws, & McKenna, 2009;Henry & Crawford, 2004;Herbert, Brookes, Markus, & Morris, 2014;Metternich, Buschmann, Wagner, Schulze-Bonhage, & Kriston, 2014;Neill, Gurvich, & Rossell, 2014;Nicodemus et al, 2014;Oh, Vidal, Taylor, & Pang, 2014;Robert et al, 1998;Sung et al, 2012;Tsantali & Economidis, 2014;Uchikawa et al, 2013;Vinogradov et al, 2003), the understanding of disorders underlying lower performance in non-verbal fluency tasks still remains limited (Pawełczyk et al, 2013;Phillips, James, Crow, & Collinson, 2004;Rinaldi, Lefebvre, & Trappeniers, 2013).…”
mentioning
confidence: 99%